Chapter Sergio Caruso, 'levità del concetto' e ricerca di mondi possibili - Henry, Barbara (Studi e saggi, 2023)
The contribution focuses through some philosophical examples in context - acroamatics, social philosophy, symbolic forms, imaginary, 'good utopia' - on Sergio Caruso's unique style and mood of thinking. Both enabled him to balance a terrific wideness of interests, knowledges and sounding/enciclopedic competences about heavy matters with a unique hint of hirony, curiosity and levity. The convergence in all of his contributions of conceptual clarity, rigour and accuracy with intellectual and pragmatic committment to the human affairs and sorrows are the key elements of Caruso's openess to the unforeseen in the social and political domains.